2018
DOI: 10.1139/cjss-2017-0081
|View full text |Cite
|
Sign up to set email alerts
|

Improved acid trap methodology for determining ammonia volatilization in wind tunnel experiments

Abstract: Nitrogen loss through ammonia volatilization is an environmental and economic concern. When acid traps are used with wind tunnels to measure ammonia volatilization, loss of solution volume is observed. As the loss mechanism affects volatilization estimates, a field study was conducted to determine if solution loss from acid traps was due to either selective loss of water through evaporation, loss of bulk solution, or a combination. Two methods for calculating air flow volume through the acid traps were also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The volume of the solution was measured before it was analyzed on the Lachat QuickChem 8500 Flow Injection Analyzer (Hach) for NH 4 + -N concentrations using a sodium salicylatebased method (QuickChem Method 12-107-06-2-A). These wind tunnels are based on designs by Lockyer (1984); details regarding win tunnel loss calculations and sampling methodology are discussed in Woodley et al (2018b). In the 2015 campaign, 1 d of sampling had to be missed because the power to the tunnels and pumps was turned off as a result heavy precipitation (97 mm) and flooding over 2 d (Supplemental Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…The volume of the solution was measured before it was analyzed on the Lachat QuickChem 8500 Flow Injection Analyzer (Hach) for NH 4 + -N concentrations using a sodium salicylatebased method (QuickChem Method 12-107-06-2-A). These wind tunnels are based on designs by Lockyer (1984); details regarding win tunnel loss calculations and sampling methodology are discussed in Woodley et al (2018b). In the 2015 campaign, 1 d of sampling had to be missed because the power to the tunnels and pumps was turned off as a result heavy precipitation (97 mm) and flooding over 2 d (Supplemental Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Ammonia volatilization is mainly governed by the concentration of the entire ammonical N (Sommer et al, 2004). Proper application technique, straw incorporation, availability of soil moisture, and avoiding application at high wind speed are some of the techniques used to reduce the rate of volatilization of the applied fertilizer N (Cao et al, 2018; Sagoo et al, 2018; Woodley et al, 2018). For instance, Cao et al (2018) reported that addition of wheat straw led to a 24% reduction in ammonia loss after the basal application.…”
Section: Developed Vs Developing Agriculturementioning
confidence: 99%
“…Further, there can be long-term effects of crop rotations on SOC accumulation and the associated improvements in soil structure. For example, a long-term water quality study on the same site found that water and nitrate partitioning and loss between surface runoff and tile drainage were impacted by crop rotation (Woodley et al, 2018). Reynolds et al (2014) reported that soil physical quality including bulk density (BD) and SOC were optimal in the top 10 cm of fertilized and unfertilized corn-oatsalfalfa-alfalfa rotations, whereas CC was suboptimal in the top 10 cm as well as over the entire 0-to-50-cm profile.…”
Section: Core Ideasmentioning
confidence: 99%
“…Water flow from the plots is routed (via surface and subsurface catch basins) to an instrumentation building that allows tile drainage and surface runoff to be separately monitored by treatment on a continuous yearround basis for water chemistry, flow timing, and flow volume. Further detail on site design, instrumentation, and operation can be found in Drury and Tan (1995), Drury et al (2014), Reynolds et al (2014), and Woodley et al (2018).…”
Section: Site Description and Treatmentsmentioning
confidence: 99%